COVID-19 and the right to health in Africa - Durojaye, Ebenezer; Mahadew, Roopanand (London : Routledge, 2024)
This collection draws upon a range of thematic and regional case studies and uses the right to health as a normative framework to explore the devastating impact of the COVID-19 pandemic in Africa. Drawing lessons from across the continent, the book discusses the challenges faced by African states seeking to ensure the availability, accessibility, and quality of health care in the context of the COVID-19 pandemic. In particular, the volume explores the impact of the pandemic on the right to health of vulnerable and marginalized groups, such as women, children, elderly persons with disabilities, refugees and asylum seekers, and people from disadvantaged communities. Due to the poor funding of the healthcare systems, access to health-related services was limited to these groups in many African countries, thereby leading to avoidable COVID-19-related deaths through shortages of vital supplies, including diagnostic tests, ventilators, and oxygen cylinders. Chapters in the volume also explore the contentious issues of vaccine mandates, equity, resource allocation, and the rights of healthcare providers during the pandemic. This collection will be of interest to students of public health, human rights, and the social sciences, as well as to academics and policymakers with an interest in the nexus between the COVID-19 pandemic and public health policy in Africa.
List of contributors Foreword by J. Michael RyanPART I: Conceptual issues 1 Introduction Ebenezer Durojaye and Roopanand Mahadew2 Discriminatory practices against women in access to health care in Kenya in the context of theCOVID-19 pandemicSoila Kigera3 Indivisibility and interdependence of human rights in the context of COVID-19Bhavna Mahadew and Roopanand MahadewPART II: Impact of COVID-19 on access to health related goods and services 4 Situation of COVID-19 vaccine inequity in developing countries Paul O. Ogendi5 COVID-19 vaccine mandate and the right to health in Africa: Should Africa toe the path of the US? Obiajulu Nnamuchi6 An intersectional perspective on inequalities in access to COVID-19 vaccines in Africa: The case of migrants Aisosa Jennifer Omoruyi7 A human rights approach to budgetary allocation and the right to health: COVID-19 and health systems in Africa Ashwanee Budoo-ScholtzPART III: Impact of COVID-19 on the right to health of disadvantaged and marginalized groups 8 Tale of two pandemics: Interrogating the impact of COVID-19 on access to maternal healthcare rights for rural women in Kenya and Uganda Muwanguzi M. Robert, Ayeranga Godfrey, and Miyienda Pauline9 Impact of COVID-19 on the sexual and reproductive health and rights of women in Eswatini Simangele Mavundla and Ann Strode10 Protection of the right to health of minorities and vulnerable groups during the COVID-19 pandemic Mansha Mohee11 The nexus between COVID-19 and sexual and reproductive health of adolescents: Bringingadolescents home; Godfrey Kangaude and Catriona Macleod12 Impact of COVID-19 on healthcare providers in Africa Adetoun T. Adebanjo13 Impact of COVID-19 on the enjoyment of rights to abortion care and the role of transparency Benson Chakaya Atonga14 Role of regional human rights bodies and national courts in addressing human rights in the context of COVID-19 pandemic Ebenezer Durojaye15 The nexus between COVID-19 and gender-based violence against women: A case of Botswana, Kenya, and NigeriaKeikantse Phele
Keywords: COVID-19 Pandemic, 2020- -- Africa; Right to health -- Africa